The answer is -a + b = 0
If she wants to solve a system of linear equations by elimination and if one equation is unknown, one of the solutions in the unknown equation must be negative:
Known equation: a + b = 4
Unknown equation: -a + b = ?
We know that a = 2 and be = 2, thus:
Unknown equation: -2 + 2 = 0
The general form of the equation is -a + b = 0
Let's check it out:
Known equation: a + b = 4
Unknown equation: -a + b = 0
________________________
Add them up: 2b = 4
b = 4/2 = 2
a + b = 4
a = 4 - b
a = 4 - 2
a = 2
So, the second equation is correct.